Redox transients of P680 associated with the incremental chlorophyll-a fluorescence yield rises elicited by a series of saturating flashes in diuron-treated photosystem II core complex of Thermosynechococcus vulcanus - Sipka, Gábor; Müller, Pavel; Brettel, Klaus; Magyar, Melinda; Kovács, László; Zhu, Qingjun; Xiao, Yanan; Han, Guangye; Lambrev, Petar H; Shen, Jian-Ren; Garab, Győző (Physiologia plantarum, 2019)
Recent chlorophyll-a fluorescence yield measurements, using single-turnover saturating flashes (STSFs), have revealed the involvement of a rate-limiting step in the reactions following the charge separation induced by the first flash. As also shown here, in diuron-inhibited PSII core complexes isolated from Thermosynechococcus vulcanus the fluorescence maximum could only be reached by a train of STSFs. In order to elucidate the origin of the fluorescence yield increments in STSF series, we performed transient absorption measurements at 819 nm, reflecting the photooxidation and re-reduction kinetics of the primary electron donor P680. Upon single flash excitation of the dark-adapted sample, the decay kinetics could be described with lifetimes of 17 ns (∼50%) and 167 ns (∼30%), and a longer-lived component (∼20%). This kinetics are attributed to re-reduction of P680•+ by the donor side of PSII. In contrast, upon second-flash (with Δt between 5 μs and 100 ms) or repetitive excitation, the 819 nm absorption changes decayed with lifetimes of about 2 ns (∼60%) and 10 ns (∼30%), attributed to recombination of the primary radical pair P680•+ Pheo•- , and a small longer-lived component (∼10%). These data confirm that only the first STSF is capable of generating stable charge separation - leading to the reduction of QA ; and thus, the fluorescence yield increments elicited by the consecutive flashes must have a different physical origin. Our double-flash experiments indicate that the rate-limiting steps, detected by chlorophyll-a fluorescence, are not correlated with the turnover of P680.
Keywords: Photosystem II Protein Complex; oxidace-redukce; Oxidation-Reduction; sinice; Cyanobacteria; Chlorophyll A; chlorofyl a; fotosystém II (proteinový komplex)